Risk factors for ESBL-producing Escherichia coli on pig farms: A longitudinal study in the context of reduced use of antimicrobials. - Wietske Dohmen (PLoS ONE, 2017)
The presence of extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-E. coli) in food animals is a public health concern. This study aimed to determine prevalence of ESBL-E. coli on pig farms and to assess the effect of reducing veterinary antimicrobial use (AMU) and farm management practices on ESBL-E. coli occurrence on pig farms. During 2011-2013, 36 Dutch conventional pig farms participated in a longitudinal study (4 sampling times in 18 months). Rectal swabs were taken from 60 pigs per farm and pooled per 6 pigs within the same age category. Presence of ESBL-E. coli was determined by selective plating and ESBL genes were characterized by microarray, PCR and gene sequencing. An extensive questionnaire on farm characteristics and AMU as Defined Daily Dosages per Animal Year (DDDA/Y) was available for the 6-month periods before each sampling moment. Associations between the presence of ESBL-E. coli-positive pigs and farm management practices were modelled with logistic regression. The number of farms with ESBL-E. coli carrying pigs decreased from 16 to 10 and the prevalence of ESBL-E. coli-positive pooled pig samples halved from 27% to 13%. Overall, the most detected ESBL genes were blaCTX-M-1, blaTEM-52 and blaCTX-M-14. The presence of ESBL-E. coli carrying pigs was not related to total AMU, but it was strongly determined by the presence or absence of cephalosporin use at the farm (OR = 46.4, p = 0.006). Other farm management factors, related with improved biosecurity, were also plausibly related to lower probabilities for ESBL-E. coli-positive farms (e.g. presence of a hygiene lock, pest control delivered by a professional). In conclusion, ESBL-E. coli prevalence decreased in pigs during 2011 and 2013 in the Netherlands. On pig farms, the use of cephalosporins was associated with the presence of ESBL-E. coli carrying pigs.